Non-base wage components as a source of wage adaptability to shocks: Evidence from European firms, 2010-2013 - Jan Babeckij; Clémence Berson; Ludmila Fadejeva; Ana Lamo; Petra Marotzke; Fernando Martins; Pawe± Strzelecki (IZA Journal of Labor Policy, 2019)
This paper provides evidence on the role of non-base wage components as a channel for firms to adjust labour costs in the event of adverse shocks. It uses data from a firm-level survey for 25 European countries that covers the period 2010-2013. We find that firms subject to nominal wage rigidities, which prevent them from adjusting base wages, are more likely to cut non-base wage components when they are hit by negative shocks. Firms thus use non-base wage components as a strategic margin to overcome base wage rigidity. We also show that while non-base wage components exhibit some degree of downward rigidity this is smaller than that observed for base wages.
Keywords: J30; J32; C81; P5; 330; Downward nominal wage rigidity; Bonuses; Firm survey; European Union; Lohnrigidität; Leistungsentgelt; Arbeitskosten; Schock; EU-Staaten